PENGARUH MANAJEMEN PENGETAHUAN TERHADAP KUALITAS PENDIDIKAN DI SMK KASATRIAN SOLO SUKOHARJO - Imam Taqorub; Supawi Pawenang; Solichul Hadi Ahmad Bakri (ITB AAS INDONESIA Surakarta, 2018)
The purpose of this study was to: (1) To describe the effect of Knowledge Management (2) To describe the influence of Teacher professionalism (3) To describe the effect of Recruitment process (4) To describe the influence of the Mastery of Information and Communication Technology on Quality Education In SMK Kasatrian Solo Sukoharjo. The research was in SMK Kasatrian Solo Sukoharjo. The population in this research were 821 teacher and students. Samples taken as many as 206. In this study, the data used are: (1)The primary data include: identity and responder. (2)Secondary data in the form of literature studies, journals, literature relating to the cases, and documentation information, and the Internet. The technique of collecting data by questionnaire, interview and documentation. Testing instrument with validity and reliability. Data analysis techniques in this study using a test classic assumptions and hypothesis testing. The classical assumption, among others, with the test data normality, autocorrelation, multicollinearity and heteroscedasticity. Hypothesis testing Regression test, t test, F test, and test Coefficient of Determination.The results of this study are: Teacher professionalism, Recruitment process and the Mastery of Information and Communication Technology can be implemented and need to be improved considering that positive and significant impact on quality education In SMK Kasatrian Solo Sukoharjo. Keywords: Knowledge Management, Teacher professionalism, Recruitment process, Mastery of Information and Communication Technology, quality education